1994
DOI: 10.1111/j.1348-0421.1994.tb01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein Produced by Helicobacter pylori

Abstract: The cells of Helicobacter pylori were suspended in the medium containing 35S-methionine. After a heat shock of the cells at 42 C for 5, 10, and 30 min, the production of proteins was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and autoradiography. Out of many proteins produced by the cells, only 66 kDa protein production was dramatically increased by heat treatment. The N-terminal amino acid sequence of 66 kDa protein was quite similar to that of 62 kDa and 54 kDa proteins previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
0
18
1
Order By: Relevance
“…As in the case of the dnaK operon, this study failed to demonstrate inducibility of the promoter by heat shock (34). On the other hand, an increase in the amount of GroEL protein after heat shock has been demonstrated previously (45). Therefore, heat induction of the GroE synthesis was assumed to be regulated posttranscriptionally (34).…”
Section: Vol 182 2000mentioning
confidence: 54%
See 1 more Smart Citation
“…As in the case of the dnaK operon, this study failed to demonstrate inducibility of the promoter by heat shock (34). On the other hand, an increase in the amount of GroEL protein after heat shock has been demonstrated previously (45). Therefore, heat induction of the GroE synthesis was assumed to be regulated posttranscriptionally (34).…”
Section: Vol 182 2000mentioning
confidence: 54%
“…The amount of GroEL increases after heat shock and acid shock (22,45). It has been proposed that GroEL may participate in protection and activity regulation of urease (12,36).…”
mentioning
confidence: 99%
“…The chaperones of the human gastric pathogen H. pylori have been studied in some detail because of their possible involvement in specific virulence mechanisms (9,12,20,25). It has been shown that the groESL, hrcA-grpE-dnaK, and cbpA-hspR-orf operons, encoding the major chaperones of H. pylori, are transcribed by an RNA polymerase containing the vegetative sigma factor 80 and regulated negatively by the transcriptional repressor HspR (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in another study, the serum TOS and OSI values decreased after proteins, may be targets of autoimmune responses 110) , and certain data have shown immunologic cross-reactions between bacterial and human HSPs 11,111,112) . For example, H. pylori-derived HSP60 (Hp-HSP60) is an important antigen that is abundantly expressed under various environmental stressors 113) . Hp-HSP60 has been found to appear on antigen-presenting cells in the germinal center in the gastric lymphoid tissues of patients infected with H. pylori 114) , and antibodies cross-reactive to both endogenous HSP60 and Hp-HSP60 have been found in the sera of H. pyloriinfected patients 115,116) .…”
Section: H Pylori and Oxidative Stressmentioning
confidence: 99%